If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3 + -2) * x = 54 Combine like terms: 3 + -2 = 1 6(1) * x = 54 Multiply 6 * 1 6x = 54 Solving 6x = 54 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '6'. x = 9 Simplifying x = 9
| 5(a+4)-(4a+4)=4(5a-2)+5 | | 900=x-.5 | | 7(2y+7)+(-36y)= | | 6x^5-4x^2+10x=0 | | -6n-1n=16 | | x^8-2x=0 | | 8(-16)/2(-8)-5(-3) | | 4-4(2a-3)=0 | | 6-3|-8r-9|=-15 | | (2x-1)/(9-x^2) | | -3|9m+2|+10=10 | | y^1/6(y^11/6+y^23/6) | | log(x+1)+2*log(x)=log(x^2+8) | | 4-9|-6-b|=-14 | | 10-10|-8k+4|=40 | | 17/x+7 | | 7.6=p-6 | | -8|3-8k|=40 | | Ln(3x)+5=7 | | 2/7x14/3 | | 3|x/9|+7=8 | | 5(3x-2)-8(2x+3)-9=51 | | -2(2x+2)=4(2-x)-12 | | 2x^2+3=y | | 61-4x=10+19 | | m/-4=-2.27 | | -5(4a-5)=2(3-10a)+19 | | -52-5x=8-8x | | 31x-13=42 | | 2(3x+1)+5(3x+1)= | | 9[v+2]-3v=2(3v+3)-11 | | m/-0.4=-2 |